Environmental and Economic Effectiveness of Resource-Saving Technologies in Cattle Meat Production - Leonidovich Vorotnikov, Igor; Pavlovich Kolotyrin, Konstantin; Borisovna Dudnikova, Elena; Yurievich Rudnev, Maksim; Ivanovich Gorbunov, Sergey (International Journal of Engineering and Technology, 2018)
CurrentÂ situation in agriculture leads to significant environmental pollution, in particular, in cattle breeding. The storage of manure significantly worsens the sanitary and epidemiological situation. In this connection, the article proposes the use of biogas plants for cattle breeding as an environmentally safe direction for the manure utilization with high economic efficiency. Particular attention is paid to the criterion of investment efficiency after use of a biogas plant, taking into account prevented environmental damage from manure storage. The economic justification of schemes for manure utilization using both a biogas plant and without it is being carried out. Â